Development of E-Learning Media Using Adobe Flash Program in a Contextual Learning Model to Improve Students' Learning Outcomes in Junior High School Geographical Research Steps Materials - Rustaminezhad, Mohammad Ali; Amosa, Abdulganiyu Alasela; Jamebozorg, Zahra (Journal of Educational Technology and Learning Creativity, 2023)
Purpose of the study: This study aims to analyze the needs of students and teachers for the development of e-learning media with the Adobe Flash program, develop e-learning media with the Adobe Flash program, determine the feasibility of e-learning media with the Adobe Flash program. Methodology: The research method used is the research and development (R&D) method developed by Dick and Carey. The sampling technique used was purposive sampling and simple random sampling. Data collection was carried out using validation sheets from media experts, material experts, educators, student trial questionnaires, observation, posttest, and documentation. Main Findings: The results of this study are needs analysis based on dominant results includes visual learning characteristics, experience of using media with frequent categories, agreeing responses with media development, green visualization, and Comic Sans MS font type. Development of research products in the form of e-learning media with the Adobe Flash program equipped with pictures, maps, videos and animations used to support contextual learning models. Novelty/Originality of this study: The novelty of this research is that the results of this study can provide convenience for independent learning through the media and make it easier to implement material on real problems in the surrounding environment.